Intractable chest pain in cardiomyopathy: treatment by a novel technique of cardiac cryodenervation with quantitative immunohistochemical assessment of success. Issue 6 (December 1993) - Gaer, J A; Gordon, L; Wharton, J; Polak, J M; Taylor, K M; McKenna, W; Parker, D J
Abstract : A novel method of cardiac denervation by cryoablation has been developed experimentally. The technique uses liquid nitrogen delivered under pressure to ablate the principal sources of cardiac innervation--namely, the adventitia surrounding the aorta, pulmonary arteries, and veins. The technique has been verified experimentally both in vivo by physiological means and in vitro by quantitative immunohistochemistry and the measurement of myocardial noradrenaline concentrations. A 35 year old woman presented with intractable precordial pain, normal epicardial coronary arteries, and hypertrophic cardiomyopathy. Her symptoms were refractory to maximal medical treatment and she was thought to be unsuitable for either conventional myocardial revascularisation, autotransplantation, or allografting with the concomitant risk of transplant coronary artery disease. She therefore underwent cardiac denervation by the method developed in the laboratory. There was quantitative immunohistochemical evidence of extrinsic cardiac denervation associated with a considerable improvement in her symptoms. This improvement persisted during a follow up period of over 16 months.